High-compaction thick positive pole piece, preparation method thereof and lithium ion battery
By regulating the matching of binders in the positive electrode slurry and adopting double-layer coating technology, the problems of particle breakage and pole fracture in the preparation of thick positive electrode slurry are solved, and the effect of high compaction density and high capacity is achieved.
Patent Information
- Application Number
- CN202411371779.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-09-29
AI Technical Summary
It is difficult to prepare thick positive electrode sheets with excellent performance, high compaction density, and low tortuosity, and there is a risk of particle breakage and pole fragment breakage.
By regulating the matching of binder in the positive electrode slurry, and using a double-layer coating, thick positive electrode sheets are designed and prepared, reducing the friction between particles and binder and current collector, and improving compaction density.
The preparation of thick positive electrode sheets with high compaction density is achieved, avoiding the risk of particle breakage and pole sheet fracture, and improving the capacity of the material.
Smart Images

Figure CN119920830A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a positive electrode sheet, and in particular to a high-density thick positive electrode sheet and a preparation method thereof, and a lithium ion battery. Background Art
[0002] Thick electrode technology has become one of the key technical directions for achieving high specific energy lithium-ion batteries and has been widely designed and applied. Although thick electrode sheets have significant advantages in improving the energy density of lithium-ion batteries, there are still some process challenges in preparing sheets with excellent performance, high compaction density, and low tortuosity. Among these challenges, how to increase the compaction density of the sheet and thus improve the capacity of the material is an important issue that needs to be solved urgently.
[0003] The existing technology mainly uses the rolling process to achieve the compaction of thick electrode plates. Conventional process optimizations include: using multiple rolling processes to achieve higher plate compaction; using hot pressing processes to achieve higher compaction density. Although these two methods can improve the compaction density to a certain extent, there is still the risk of particle crushing and plate breaking caused by particle overpressure, and the fundamental problem has not been solved. Summary of the invention
[0004] Problem that the invention aims to solve
[0005] In view of the above situation, it is necessary to provide a thick positive electrode sheet with no risk of particle crushing and electrode sheet breakage and with high compaction density, and a method for preparing a thick positive electrode sheet that can increase the compaction density of the electrode sheet without over-pressing.
[0006] Solutions for solving problems
[0007] In order to improve the compaction density and rolling effect of thick positive electrode sheets, the present invention starts from the design and preparation of thick positive electrode sheets, adjusts the combination of binders in the positive electrode slurry and adopts a double-layer coating method to design and prepare the sheets, thereby reducing the friction between the sheet particles and the binder and the current collector, and improving the compaction density of the thick positive electrode, which essentially solves the problems of particle crushing and sheet breakage caused by rolling of the thick positive electrode.
[0008] Specifically, the present invention provides a high-density thick positive electrode sheet, the high-density thick positive electrode sheet comprising a current collector, a first positive electrode coating on the current collector, and a second positive electrode coating on the first positive electrode coating.
[0009] The first positive electrode coating is formed by a first positive electrode slurry, wherein the first positive electrode slurry includes a first positive electrode active main material, a first positive electrode binder, a first conductive agent, a second conductive agent, and a second positive electrode binder.
[0010] The second positive electrode coating is formed by a second positive electrode slurry, wherein the second positive electrode slurry includes a second positive electrode active main material, a third positive electrode binder, a third conductive agent, a fourth conductive agent and a fourth positive electrode binder.
[0011] The molecular weight of the second positive electrode binder is greater than 1 million and the crystallinity is greater than 45%.
[0012] The molecular weight of the fourth positive electrode binder is less than 700,000 and the crystallinity is less than 40%.
[0013] According to the high-compacted thick positive electrode sheet described above, the molecular weight of each of the first positive electrode binder and the third positive electrode binder is greater than 1 million and the crystallinity is greater than 45%;
[0014] The molecular weights and crystallinities of the first positive electrode binder, the second positive electrode binder, and the third positive electrode binder are the same or different.
[0015] According to the high-compacted thick positive electrode sheet described above, the first positive electrode binder, the second positive electrode binder, the third positive electrode binder and the fourth positive electrode binder are each independently selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene and oily acrylic homopolymer.
[0016] According to the high-compacted thick positive electrode sheet described above, the first conductive agent, the second conductive agent, the third conductive agent and the fourth conductive agent are each independently selected from one or more of oily single-walled carbon nanotubes, oily multi-walled carbon nanotubes, conductive carbon fibers, graphite, graphene, and carbon black, and they are the same or different;
[0017] Preferably, the first conductive agent and the third conductive agent are selected from one or more of conductive carbon fiber, graphite, graphene, and carbon black, the second conductive agent is oily single-walled carbon nanotube, and the fourth conductive agent is oily multi-walled carbon nanotube.
[0018] According to the high-compacted thick positive electrode sheet described above, the first positive electrode active main material and the second positive electrode active main material are independently selected from one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese iron phosphate, lithium manganese oxide, and nickel cobalt manganese oxide;
[0019] The first positive electrode active main material and the second positive electrode active main material are the same as or different from each other.
[0020] According to the high compacted thick positive electrode sheet described above, the first positive electrode slurry further comprises a first positive electrode active material additive, and / or the second positive electrode slurry further comprises a second positive electrode active material additive,
[0021] The first positive electrode active material additive and the second positive electrode active material additive are each independently selected from one or more of Li2S, Li2NiO2, Li5FeO4, Li2O, and Li2O2;
[0022] The first positive electrode active material additive is the same as or different from the second positive electrode active material additive,
[0023] Preferably, the addition amounts of the first positive electrode active material additive and the second positive electrode active material additive are both selected from 0.5-2.5 mass %.
[0024] According to the high-compacted thick positive electrode sheet described above, the weight ratio of each material in the first positive electrode coating is: 96.5-97.8 mass% of the first positive electrode active main material, 1.0-2.3 mass% of the first positive electrode binder, 0.2-0.8 mass% of the first conductive agent, 0.0005-0.024 mass% of the second conductive agent, and 0.00075-0.032 mass% of the second positive electrode binder;
[0025] Preferably, the weight proportion of each material in the first positive electrode coating is: 96.8-97.3 mass % of the first positive electrode active main material, 1.0-1.5 mass % of the first positive electrode binder, 0.3-0.6 mass % of the first conductive agent, 0.001-0.009 mass % of the second conductive agent, and 0.0015-0.012 mass % of the second positive electrode binder.
[0026] According to the high-compacted thick positive electrode plate described above, the weight proportion of each material in the second positive electrode coating is: 97-97.8 mass% of the second positive electrode active main material, 0.8-1.3 mass% of the third positive electrode binder, 0.5-1.0 mass% of the third conductive agent, 0.00075-0.0175 mass% of the fourth conductive agent, and 0.00015-0.04 mass% of the fourth positive electrode binder.
[0027] According to the above-mentioned high compaction thick positive electrode sheet, the thickness of the thick positive electrode sheet is 160-240 μm; the compaction density of the thick positive electrode sheet is 3.28-3.5 g / cm 3 .
[0028] The present invention also provides a method for preparing a high-density thick positive electrode sheet, the preparation method comprising the following steps:
[0029] Step S1: determining the required surface density of the positive electrode sheet;
[0030] Step S2: preparing a first positive electrode slurry and a second positive electrode slurry,
[0031] The first positive electrode slurry is formed by dispersing a first positive electrode active main material, a first positive electrode binder, a first conductive agent, a second conductive agent, and a second positive electrode binder in a solvent.
[0032] The second positive electrode slurry is formed by dispersing a second positive electrode active main material, a third positive electrode binder, a third conductive agent, a fourth conductive agent and a fourth positive electrode binder in a solvent.
[0033] The molecular weight of the second positive electrode binder is greater than 1 million and the crystallinity is greater than 45%.
[0034] The molecular weight of the fourth positive electrode binder is less than 700,000 and the crystallinity is less than 40%;
[0035] Step S3: according to the surface density of the positive electrode sheet determined in step S1, the first positive electrode slurry is coated on the current collector to form a first positive electrode coating, and the second positive electrode slurry is coated on the first positive electrode coating to form a second positive electrode coating, and then dried to obtain a electrode sheet;
[0036] Step S4: Roll-press the electrode sheet obtained in step S3 to obtain a high-density thick positive electrode sheet.
[0037] According to the preparation method described above, in step S2, the second conductive agent and the second positive electrode binder are first dispersed in a solvent to form a first conductive slurry, and then the first conductive slurry is mixed with the first positive electrode active main material, the first positive electrode binder and the first conductive agent and dispersed in the solvent to obtain a first positive electrode slurry; and / or,
[0038] Firstly, the fourth conductive agent and the fourth positive electrode binder are dispersed in a solvent to form a second conductive slurry, and then the second conductive slurry is mixed with a second positive electrode active material, a third positive electrode binder and a third conductive agent and dispersed in a solvent to obtain a second positive electrode slurry.
[0039] According to the preparation method described above, the surface density of the positive electrode sheet determined in step S1 is 400-800 g / m 2 , preferably 480-630g / m 2 .
[0040] According to the preparation method described above, in step S2, the viscosity of the first positive electrode slurry and the second positive electrode slurry is 4000-6000 Pa·s, the solid content is 68-75% by mass, the average particle size of the slurry particles is less than 60 μm, and the scratch is less than 40 μm.
[0041] According to the preparation method described above, in step S3, the coating surface density of the first positive electrode slurry is 216-284 g / m 2The coating surface density of the second positive electrode slurry is 264-347g / m 2 .
[0042] According to the preparation method described above, in step S4, the roller compaction density is 3.28-3.5 g / cm 3 ,
[0043] Preferably, the rolling pressure is 45-100T.
[0044] The present invention further provides a lithium ion battery, which comprises the thick positive electrode sheet described above or the thick positive electrode sheet obtained by the preparation method described above.
[0045] Effects of the Invention
[0046] The above technical solution of the present invention has the following beneficial effects:
[0047] (1) The present invention reduces the friction between particles and particles, particles and binder, and particles and current collector in the electrode sheet by regulating the molecular weight and crystallinity of the binder in the positive electrode slurry, thereby improving the adhesion between the positive electrode particles and the current collector; and improves the compaction density of thick positive electrode sheets by adopting a two-layer coating structure;
[0048] (2) The present invention reduces the friction between the binder and the material particles by designing a thick positive electrode sheet and regulating the binder composition between different coatings in the slurry. The double-layer coating preparation process is used to further optimize the distribution of the binder in the thick positive electrode sheet, thereby improving the adhesion between the positive electrode particles and the current collector and increasing the compaction density of the thick positive electrode sheet. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 It is a graph showing the sheet resistance of the positive electrode sheets of Examples 1-5 and Comparative Examples 1 and 2.
[0050] Figure 2 It is a graph showing the peel strength of the positive electrode sheets of Examples 1-5 and Comparative Examples 1 and 2. DETAILED DESCRIPTION
[0051] Various exemplary embodiments, features and aspects of the present invention will be described in detail below. The word "exemplary" used here means "used as an example, embodiment or illustrative". Any embodiment described here as "exemplary" is not necessarily interpreted as being superior or better than other embodiments.
[0052] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.
[0053] In this specification, the word "may" means both performing a certain process and not performing a certain process.
[0054] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.
[0055] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values A and B.
[0056] In this specification, unless otherwise specified, "%" means mass percentage.
[0057] First aspect
[0058] The first aspect of the present invention provides a high-density thick positive electrode sheet. The high-density thick positive electrode sheet of the present invention comprises a current collector, a first positive electrode coating on the current collector, and a second positive electrode coating on the first positive electrode coating.
[0059] The first positive electrode coating is formed by a first positive electrode slurry, and the first positive electrode slurry includes a first positive electrode active main material, a first positive electrode binder, a first conductive agent, a second conductive agent and a second positive electrode binder.
[0060] The second positive electrode coating layer is formed by a second positive electrode slurry, and the second positive electrode slurry includes a second positive electrode active main material, a third positive electrode binder, a third conductive agent, a fourth conductive agent and a fourth positive electrode binder.
[0061] In the present invention, the molecular weight of the first positive electrode binder, the second positive electrode binder and the third positive electrode binder are greater than 1 million and the crystallinity is greater than 45%. The molecular weight and crystallinity of the first positive electrode binder, the second positive electrode binder and the third positive electrode binder can be the same or different.
[0062] Specifically, the molecular weight of the first positive electrode binder, the second positive electrode binder, and the third positive electrode binder may be independently greater than 1 million and less than 1.5 million, for example, 1.01 million, 1.05 million, 1.1 million, 1.15 million, 1.2 million, 1.25 million, 1.3 million, 1.35 million, 1.4 million, 1.45 million, 1.5 million, etc. The crystallinity of the first positive electrode binder, the second positive electrode binder, and the third positive electrode binder may be independently greater than 45% and less than 65%, for example, 46%, 47%, 48%, 49%, 50%, 52%, 55%, 60%, 65%, etc.
[0063] In the present invention, the molecular weight of the fourth positive electrode binder is less than 700,000 and the crystallinity is less than 40%. For example, the molecular weight of the fourth positive electrode binder may be less than 700,000 but greater than or equal to 300,000, for example, it may be 690,000, 650,000, 600,000, 550,000, 500,000, 450,000, 400,000, 350,000, 300,000, etc. The crystallinity of the fourth positive electrode binder may be less than 40% but greater than or equal to 25%, for example, it may be 39%, 38%, 37%, 36%, 35%, 34%, 33%, 32%, 31%, 30%, 29%, 28%, 27%, 26%, etc.
[0064] In the high-compacted thick positive electrode sheet of the present invention, by using a binder with a larger molecular weight and a larger degree of crystallinity in the first positive electrode coating and a binder with a smaller molecular weight and a smaller degree of crystallinity in the second positive electrode coating, the friction between particles and particles, particles and binder, and particles and current collector in the sheet can be reduced, and relative slip is generated during the rolling process, thereby improving the compaction density of the thick electrode sheet and ensuring the rolling effect of the sheet.
[0065] In a specific embodiment of the present invention, the first positive electrode binder, the second positive electrode binder, the third positive electrode binder and the fourth positive electrode binder can be independently selected from one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and oily acrylic acid homopolymer (oil-based polyacrylic acid PAA). The first positive electrode binder, the second positive electrode binder, the third positive electrode binder and the fourth positive electrode binder can be the same or different, and preferably they are the same binder material.
[0066] In the present invention, the first conductive agent, the second conductive agent, the third conductive agent and the fourth conductive agent can be independently selected from one or more of oily single-walled carbon nanotubes, oily multi-walled carbon nanotubes, conductive carbon fibers, acetylene black, natural graphite, artificial graphite, graphene, and carbon black, and they can be the same or different.
[0067] In some preferred embodiments, the first conductive agent and the third conductive agent may be selected from one or more of conductive carbon fiber, acetylene black, natural graphite, artificial graphite, graphene, and carbon black, the second conductive agent may be an oily single-walled carbon nanotube, and the fourth conductive agent may be an oily multi-walled carbon nanotube. By including single-walled carbon nanotubes in the first positive electrode coating and multi-walled carbon nanotubes in the second positive electrode coating, good rate performance can be ensured. In addition, by combining the first conductive agent and the second conductive agent with different conductive abilities in the first positive electrode coating, and by combining the third conductive agent and the fourth conductive agent with different conductive abilities in the second positive electrode coating, the conductive performance of the coating can be improved while ensuring good rate performance, while reducing costs.
[0068] In the present invention, the first positive electrode active material and the second positive electrode active material can be independently selected from one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese iron phosphate, lithium manganese oxide, and lithium nickel cobalt manganese oxide. The first positive electrode active material and the second positive electrode active material can be the same or different.
[0069] In addition, the first positive electrode slurry of the present invention may also optionally include a first positive electrode active material additive, and the second positive electrode slurry may also optionally include a second positive electrode active material additive. In the present invention, the positive electrode active material additive is mainly a lithium supplement. Specifically, the first positive electrode active material additive and the second positive electrode active material additive can be independently selected from one or more of lithium sulfide (Li2S), lithium nickelate (Li2NiO2), lithium ferrite (Li5FeO4, LFO), lithium oxide (Li2O), and lithium peroxide (Li2O2). The first positive electrode active material additive and the second positive electrode active material additive may be the same or different. By adding the above additives, the lithium loss of the positive electrode material can be compensated. The addition amount of the first positive electrode active material additive and the second positive electrode active material additive are both selected from 0.5-2.5 mass%, for example, 0.5 mass%, 0.8 mass%, 1.0 mass%, 1.2 mass%, 1.5 mass%, 1.8 mass%, 2.0 mass%, 2.2 mass%, 2.5 mass%, etc.
[0070] In the present invention, the proportions of the materials used in the first positive electrode coating and the second positive electrode coating are regulated. Specifically, the weight proportions of the materials used in the first positive electrode coating may be: 96.5-97.8 mass % of the first positive electrode active main material, 1.0-2.3 mass % of the first positive electrode binder, 0.2-0.8 mass % of the first conductive agent, 0.0005-0.024 mass % of the second conductive agent, and 0.00075-0.032 mass % of the second positive electrode binder.
[0071] In some preferred embodiments, the weight proportion of each material used in the first positive electrode coating may be: 96.8-97.3 mass % of the first positive electrode active main material, 1.0-1.5 mass % of the first positive electrode binder, 0.3-0.6 mass % of the first conductive agent, 0.001-0.009 mass % of the second conductive agent, and 0.0015-0.012 mass % of the second positive electrode binder.
[0072] In the present invention, the weight proportion of each material used in the second positive electrode coating can be: 97-97.8 mass% of the second positive electrode active main material, 0.8-1.3 mass% of the third positive electrode binder, 0.5-1.0 mass% of the third conductive agent, 0.00075-0.0175 mass% of the fourth conductive agent, and 0.00015-0.04 mass% of the fourth positive electrode binder.
[0073] In the present invention, the thickness of the first positive electrode coating may be 70-110 μm, the thickness of the second positive electrode coating may be 90-130 μm, and the thickness of the high-compacted thick positive electrode sheet may be 160-240 μm. For example, the thickness of the first positive electrode coating may be 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, etc., the thickness of the second positive electrode coating may be 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, etc., and the thickness of the high-compacted thick positive electrode sheet may be 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, etc. The compaction density of the high-compacted thick positive electrode sheet of the present invention may be 3.28-3.5 g / cm 3 .
[0074] The current collector used for the positive electrode sheet of the present invention is not particularly limited, and conventional current collectors in the art can be used, such as aluminum foil.
[0075] Second aspect
[0076] The second aspect of the present invention provides a method for preparing the high-compacted thick positive electrode sheet in the first aspect.
[0077] The method for preparing the high-density thick positive electrode sheet of the present invention comprises the following steps:
[0078] Step S1: determining the required surface density of the positive electrode sheet;
[0079] Step S2: preparing a first positive electrode slurry and a second positive electrode slurry,
[0080] The first positive electrode slurry is formed by dispersing a first positive electrode active material, a first positive electrode binder, a first conductive agent, a second conductive agent, and a second positive electrode binder in a solvent.
[0081] The second positive electrode slurry is formed by dispersing a second positive electrode active main material, a third positive electrode binder, a third conductive agent, a fourth conductive agent and a fourth positive electrode binder in a solvent.
[0082] The molecular weight of the second positive electrode binder is greater than 1 million and the crystallinity is greater than 45%.
[0083] The molecular weight of the fourth positive electrode binder is less than 700,000 and the crystallinity is less than 40%;
[0084] Step S3: according to the surface density of the positive electrode sheet determined in step S1, the first positive electrode slurry is coated on the current collector to form a first positive electrode coating, and the second positive electrode slurry is coated on the first positive electrode coating to form a second positive electrode coating, and then dried to obtain a electrode sheet;
[0085] Step S4: Roll-press the electrode sheet obtained in step S3 to obtain a high-density thick positive electrode sheet.
[0086] Each step is described in detail below.
[0087] Step S1
[0088] In step S1, the surface density parameters of the positive electrode sheet required are calculated and output through the battery cell design. In some specific embodiments, the surface density of the positive electrode sheet can range from 400 to 800 g / m 2 , preferably 480-630g / m 2 For example, the surface density of the positive electrode sheet can be 420g / m 2 , 450g / m 2 , 500g / m 2 , 520g / m 2 , 550g / m 2 , 580g / m 2 , 600g / m 2 , 620g / m 2 wait.
[0089] Step S2
[0090] In step S2 , a first positive electrode slurry and a second positive electrode slurry are prepared.
[0091] The types, proportions, molecular weights, crystallinity, etc. of the materials used in the first positive electrode slurry and the second positive electrode slurry in step S2 are the same as those in the first aspect above, and are not repeated here. As described in the first aspect above, the molecular weight of the second positive electrode binder is greater than 1 million and the crystallinity is greater than 45%; the molecular weight of the fourth positive electrode binder is less than 700,000 and the crystallinity is less than 40%.
[0092] In the present invention, the first positive electrode slurry can be formed by dispersing the first positive electrode active material, the first positive electrode binder, the first conductive agent, the second conductive agent and the second positive electrode binder in a solvent.
[0093] In some preferred embodiments, the second conductive agent and the second positive electrode binder can be first dispersed in a solvent to form a first conductive slurry, and then the first conductive slurry is mixed with the first positive electrode active material, the first positive electrode binder and the first conductive agent and dispersed in a solvent to obtain a first positive electrode slurry.
[0094] In the first conductive paste of the present invention, the content of the second conductive agent may be about 1-3% by mass of the total amount of the first conductive paste, the content of the second positive electrode binder may be about 1.5-4% by mass of the total amount of the first conductive paste, and the remainder is a solvent. The viscosity of the first conductive paste and the second conductive paste may each be less than 3000 Pa·s, for example, 2900 Pa·s, 2700 Pa·s, 2500 Pa·s, 2200 Pa·s, 2000 Pa·s, 1800 Pa·s, 1500 Pa·s, etc.
[0095] In the present invention, the second positive electrode slurry can be formed by dispersing the second positive electrode active material, the third positive electrode binder, the third conductive agent, the fourth conductive agent and the fourth positive electrode binder in a solvent.
[0096] In some preferred embodiments, the fourth conductive agent and the fourth positive electrode binder can be first dispersed in a solvent to form a second conductive slurry, and then the second conductive slurry is mixed with the second positive electrode active material, the third positive electrode binder and the third conductive agent and dispersed in a solvent to obtain a second positive electrode slurry.
[0097] In the second conductive paste of the present invention, the content of the fourth conductive agent may be about 1.5-3.5% by mass of the total amount of the second conductive paste, the content of the fourth positive electrode binder may be about 0.3-8% by mass of the total amount of the second conductive paste, and the remainder is solvent.
[0098] By preparing the first conductive paste and / or the second conductive paste first, the second conductive agent and / or the fourth conductive agent can be better dispersed in the positive electrode paste.
[0099] In step S2, the solvents used for the first positive electrode slurry, the second positive electrode slurry, the first conductive slurry, and the second conductive slurry are not particularly limited, and commonly used solvents in the art may be used, such as N-methylpyrrolidone (NMP), butanediol methyl ether, dimethyl sulfoxide, etc. The solvents used for the first positive electrode slurry, the second positive electrode slurry, the first conductive slurry, and the second conductive slurry may be the same or different, preferably the same.
[0100] In a specific embodiment, the first positive electrode active material, the first positive electrode binder, the first conductive agent, the second conductive agent and the second positive electrode binder (or the first conductive slurry is used instead of the second conductive agent and the second positive electrode binder) and the optional first positive electrode active material additive are mixed in a certain proportion, and then a certain amount of solvent is added for dispersion, thereby preparing a first positive electrode coating; the second positive electrode active material, the third positive electrode binder, the third conductive agent, the fourth conductive agent and the fourth positive electrode binder (or the second conductive slurry is used instead of the fourth conductive agent and the fourth positive electrode binder) and the optional second positive electrode active material additive are mixed in a certain proportion, and then a certain amount of solvent is added for dispersion, thereby preparing a second positive electrode slurry.
[0101] In the present invention, the viscosity of the first positive electrode slurry and the second positive electrode slurry can be 4000-6000 Pa·s, the solid content can be 68-75% by mass, the average particle size of the slurry particles is less than 60 μm, and the scratch is less than 40 μm.
[0102] Specifically, the viscosity of each of the first positive electrode slurry and the second positive electrode slurry may be 4200Pa·s, 4500Pa·s, 4800Pa·s, 5000Pa·s, 5200Pa·s, 5500Pa·s, 5800Pa·s, etc. The solid content of each of the first positive electrode slurry and the second positive electrode slurry may be 69 mass%, 70 mass%, 71 mass%, 72 mass%, 73 mass%, 74 mass%, etc. The average particle size of the slurry particles may be 59μm, 55μm, 50μm, 45μm, 40μm, 35μm, 30μm, 25μm, 20μm, 15μm, 10μm, 5μm, 1μm, etc. The scratches of each of the first positive electrode slurry and the second positive electrode slurry may be 39μm, 35μm, 30μm, 25μm, 20μm, 15μm, 10μm, etc.
[0103] Step S3
[0104] In the present invention, a two-layer coating method is adopted for slurry coating, thereby further optimizing the distribution of the binder in the thick electrode sheet, which not only improves the adhesion between the positive electrode particles and the current collector, but also regulates the binder composition between different coatings through the slurry, further reducing the friction between the positive electrode material particles and the binder and improving the compaction density of the thick electrode sheet.
[0105] Specifically, according to the surface density determined in step S1, the first positive electrode slurry is coated on one surface of the current collector to form a first positive electrode coating; the second positive electrode slurry is coated on the surface of the first positive electrode coating to form a second positive electrode coating, and then dried to obtain a positive electrode sheet.
[0106] In the present invention, the coating surface density of the first positive electrode slurry can be 216-284g / m 2 , for example, 220g / m 2 , 230g / m 2 , 240g / m 2 , 250g / m 2 , 260g / m 2 , 270g / m 2 , 275g / m 2 , 280g / m 2 The coating surface density of the second positive electrode slurry can be 264-347g / m 2 , for example, 270g / m 2 , 280g / m 2 , 290g / m 2 , 300g / m 2 , 310g / m 2 , 320g / m 2 , 330g / m 2 , 340g / m 2 , 345g / m 2 The sum of the coating surface density of the first positive electrode slurry and the coating surface density of the second positive electrode slurry is the actual surface density of the positive electrode sheet.
[0107] In the present invention, the temperature and time for drying after coating the first positive electrode slurry and the second positive electrode slurry are not particularly limited, for example, the temperature may be 60-120° C., and the time may be 20-40 min.
[0108] Step S4
[0109] In step S4, the electrode sheet obtained in step S3 is rolled to obtain a high-density thick positive electrode sheet. The rolling compaction density in step S4 can be 3.28-3.5 g / cm 3 The thickness of the finally obtained high-compacted thick positive electrode sheet can be 160-240 μm, and the rolling pressure can be 45-100T.
[0110] The third aspect
[0111] A third aspect of the present invention provides a lithium-ion battery, which comprises the thick positive electrode sheet described above or the thick positive electrode sheet obtained by the preparation method described above.
[0112] Example
[0113] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0114] Preparation of slurry used in Examples 1-5
[0115] Preparation of the first conductive paste: The oily single-walled carbon nanotubes CNTs as the second conductive agent and the PVDF as the second positive electrode binder are dry-mixed in a weight ratio of 1:6, and then the solvent NMP is added for high-speed dispersion. The preparation of the conductive paste is completed when the viscosity is 2600mPa·s and the solid content is 1.2% by mass.
[0116] Preparation of the first positive electrode slurry: The first positive electrode active material NCM811, the first positive electrode binder PVDF, the first conductive agent acetylene black, the first conductive slurry, and the first positive electrode active material additive lithium ferrite are dry-mixed in a ratio of 97 mass%, 1.2 mass%, 0.3 mass%, 0.6 mass%, and 1.35 mass%, and the solvent NMP is added for further mixing to obtain a slurry with a slurry viscosity of 5500 mPa·s.
[0117] After the slurry is prepared, a 200-mesh screen is used to screen the slurry. The viscosity of the screened slurry is tested using a viscometer with a 3# rotor and 12 rpm.
[0118] In addition, the particle and scratch test is carried out as follows: drop the slurry into the deepest part of the scraper fineness meter groove, use the scraper to vertically contact the flat plate to scrape the slurry from the maximum scale to the minimum scale within 1-2 seconds, and observe the uniformly exposed particles along the incident angle of 20-30° within 5 seconds after scraping. If there are 5-10 particles in the 3mm strip of the slurry, it is recorded as the maximum fineness of the slurry. After the parameters of the slurry are qualified, vacuum it and store it slowly.
[0119] Preparation of the second conductive paste: The oily multi-walled carbon nanotubes as the fourth conductive agent and the PVDF as the fourth positive electrode binder are dry-mixed in a weight ratio of 2:3, and then the solvent NMP is added for high-speed dispersion. The preparation of the conductive paste is completed when the viscosity is 2300mPa·s and the solid content is 4.6% by mass.
[0120] Preparation of the second positive electrode slurry: dry powder mixing of the second positive electrode active material NCM622, the third positive electrode binder PVDF, the third conductive agent conductive carbon black, the second conductive slurry, and the second positive electrode active material additive lithium ferrite in the ratio of 97.3 mass%, 1.0 mass%, 0.6 mass%, 0.1 mass%, and 1.0 mass%, adding solvent NMP for further mixing to obtain a slurry with a slurry viscosity of 5000 mPa·s. The viscosity, particle and scratch tests are the same as those in the first positive electrode slurry, and the slurry parameters are vacuumed and stored slowly after passing the test.
[0121] The particle and scratch test results of the first slurry and the second slurry prepared in Comparative Example 1, Comparative Example 2 and Examples 1 to 5 are shown in Table 1.
[0122] Table 1
[0123]
[0124]
[0125] The two slurries were coated in a double-layer manner, where the first coating area was close to the current collector. The first coating area used the first positive electrode slurry, and the coating surface density of the first positive electrode slurry was 246 g / m 2 ; The second coating area is coated on the first coating area, and the slurry adopts the second positive electrode slurry, and the coating surface density of the second positive electrode slurry is 284g / m 2 .
[0126] Examples 1-5 all adopt a double-layer coating method to prepare the electrode sheets, wherein the formula of each component in the first positive electrode slurry and the second positive electrode slurry remains unchanged, the molecular weight and crystallinity of the first positive electrode binder PVDF in the first positive electrode slurry and the second positive electrode binder PVDF in the first conductive slurry are listed in Table 2, and the molecular weight and crystallinity of the third positive electrode binder PVDF in the second positive electrode slurry and the fourth positive electrode binder PVDF in the second conductive slurry are listed in Table 3.
[0127] Comparative Example 1: The first positive electrode slurry is used for single-layer coating, and the coating surface density is 530 g / m 2 .
[0128] Comparative Example 2: The first coating area uses the second positive electrode slurry, and the coating surface density is 246 g / m 2 The second coating area is coated on the first coating area, and the second coating area adopts the first positive electrode slurry, and the coating surface density is 284g / m 2 .
[0129] Table 2: The molecular weight and crystallinity of the first positive electrode binder PVDF in the first positive electrode slurry and the second positive electrode binder PVDF in the first conductive slurry are as follows:
[0130]
[0131]
[0132] Table 3: The molecular weight and crystallinity of the third positive electrode binder in the second positive electrode slurry and the fourth positive electrode binder PVDF in the second conductive slurry are as follows:
[0133]
[0134] In accordance with the above requirements, the first positive electrode slurry and the second positive electrode slurry were prepared in Examples 1-5 and Comparative Examples 1 and 2. The electrode sheets were coated according to step S4. After the first positive electrode slurry was dried at 90°C, the second positive electrode slurry was coated. The electrode sheets were then dried at 90°C for 30 minutes to obtain the electrode sheets. The electrode sheets of the Examples and Comparative Examples were rolled at a rolling pressure of 60T to obtain good electrode sheets. All the electrode sheets were rolled at 3.45g / cm 3 The pole piece is rolled according to the designed compaction. The pole piece thickness and rolling state are shown in Table 4:
[0135] Table 4
[0136]
[0137]
[0138] By calculating the electrode states and actual compaction densities of different embodiments and comparative examples, it can be seen that the compaction density of the electrode is efficiently improved by regulating the molecular weight and crystallinity of the binder in the slurry and adopting a double-layer coating method, which further shows that the thick positive electrode design of the present invention has a significant effect on the compaction of the thick positive electrode. It also shows that different binder combinations do reduce the friction between particles and particles, particles and binders, and particles and current collectors in the electrode, resulting in relative slip during the rolling process, thereby improving the compaction of the thick positive electrode and ensuring the rolling effect of the electrode.
[0139] In addition, the film resistance and peel strength of the electrode sheets of the embodiment and the comparative example were tested, and the results are as follows: Figure 1 and Figure 2 shown.
[0140] according to Figure 1 The diaphragm resistance and Figure 2The peel strength data shown indicate that the thick positive electrode plate designed in the present invention has a higher compaction density, and the compaction density reduces the diaphragm resistance of the plate. This is because when the compaction density increases, the contact between the plate particles is closer, and the electron path between the plate particles and the conductive agent is reduced, thereby reducing the diaphragm resistance of the plate. At the same time, when the compaction density of the plate increases, the combination of the binder in the present invention improves the distribution of the binder and ultimately improves the peel strength of the plate.
[0141] The technical solution provided by the present invention is easy to understand by professionals in the field. According to the disclosure and guidance of the above description, those skilled in the art will further expand and improve the above embodiments. Therefore, the present invention is not limited to the above-mentioned specific embodiments. Those skilled in the art should understand that any obvious improvements, replacements or modifications made on the basis of the present invention belong to the protection scope of the present invention. In addition, although some specific restrictive terms are used in this specification, these terms are only for further illustrating the technical solution of the present invention and do not constitute any limitation to the present invention.
Claims
1. A high-density thick positive electrode plate, characterized in that: The high-density thick positive electrode sheet comprises a current collector, a first positive electrode coating on the current collector, and a second positive electrode coating on the first positive electrode coating. The first positive electrode coating is formed by a first positive electrode slurry, wherein the first positive electrode slurry includes a first positive electrode active main material, a first positive electrode binder, a first conductive agent, a second conductive agent, and a second positive electrode binder. The second positive electrode coating is formed by a second positive electrode slurry, wherein the second positive electrode slurry includes a second positive electrode active main material, a third positive electrode binder, a third conductive agent, a fourth conductive agent and a fourth positive electrode binder. The molecular weight of the second positive electrode binder is greater than 1 million and the crystallinity is greater than 45%. The molecular weight of the fourth positive electrode binder is less than 700,000 and the crystallinity is less than 40%.
2. The high-compacted thick positive electrode sheet according to claim 1, wherein the molecular weight of each of the first positive electrode binder and the third positive electrode binder is greater than 1 million and the crystallinity is greater than 45%; The molecular weights and crystallinities of the first positive electrode binder, the second positive electrode binder, and the third positive electrode binder are the same or different.
3. The high-compacted thick positive electrode sheet according to claim 2, wherein the first positive electrode binder, the second positive electrode binder, the third positive electrode binder and the fourth positive electrode binder are each independently selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene and oily acrylic homopolymer.
4. The high-compacted thick positive electrode sheet according to any one of claims 1 to 3, wherein the first conductive agent, the second conductive agent, the third conductive agent and the fourth conductive agent are each independently selected from one or more of oily single-walled carbon nanotubes, oily multi-walled carbon nanotubes, conductive carbon fibers, graphite, graphene, and carbon black, and they are the same or different; Preferably, the first conductive agent and the third conductive agent are selected from one or more of conductive carbon fiber, graphite, graphene, and carbon black, the second conductive agent is oily single-walled carbon nanotube, and the fourth conductive agent is oily multi-walled carbon nanotube.
5. The high-compacted thick positive electrode sheet according to any one of claims 1 to 4, wherein the first positive electrode active main material and the second positive electrode active main material are independently selected from one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese iron phosphate, lithium manganese oxide, and nickel cobalt lithium manganese oxide; The first positive electrode active main material and the second positive electrode active main material are the same as or different from each other.
6. The high-compacted thick positive electrode sheet according to any one of claims 1 to 5, wherein the first positive electrode slurry further comprises a first positive electrode active material additive, and / or the second positive electrode slurry further comprises a second positive electrode active material additive, The first positive electrode active material additive and the second positive electrode active material additive are each independently selected from one or more of Li2S, Li2NiO2, Li5FeO4, Li2O, and Li2O2; The first positive electrode active material additive is the same as or different from the second positive electrode active material additive; Preferably, the addition amounts of the first positive electrode active material additive and the second positive electrode active material additive are both selected from 0.5-2.5 mass %.
7. The high-compacted thick positive electrode sheet according to any one of claims 2 to 6, wherein the weight ratio of each material in the first positive electrode coating is: 96.5-97.8 mass% of the first positive electrode active main material, 1.0-2.3 mass% of the first positive electrode binder, 0.2-0.8 mass% of the first conductive agent, 0.0005-0.024 mass% of the second conductive agent, and 0.00075-0.032 mass% of the second positive electrode binder; Preferably, the weight proportion of each material in the first positive electrode coating is: 96.8-97.3 mass % of the first positive electrode active main material, 1.0-1.5 mass % of the first positive electrode binder, 0.3-0.6 mass % of the first conductive agent, 0.001-0.009 mass % of the second conductive agent, and 0.0015-0.012 mass % of the second positive electrode binder.
8. A high-compacted thick positive electrode plate according to any one of claims 2 to 7, wherein the weight proportion of each material in the second positive electrode coating is: 97-97.8% by mass of the second positive electrode active main material, 0.8-1.3% by mass of the third positive electrode binder, 0.5-1.0% by mass of the third conductive agent, 0.00075-0.0175% by mass of the fourth conductive agent, and 0.00015-0.04% by mass of the fourth positive electrode binder.
9. The high compacted thick positive electrode sheet according to any one of claims 1 to 7, wherein the thickness of the thick positive electrode sheet is 160-240 μm; the compacted density of the thick positive electrode sheet is 3.28-3.5 g / cm 3 .
10. A method for preparing a high-density thick positive electrode sheet, characterized in that: The preparation method comprises the following steps: Step S1: determining the required surface density of the positive electrode sheet; Step S2: preparing a first positive electrode slurry and a second positive electrode slurry, The first positive electrode slurry is formed by dispersing a first positive electrode active material, a first positive electrode binder, a first conductive agent, a second conductive agent, and a second positive electrode binder in a solvent. The second positive electrode slurry is formed by dispersing a second positive electrode active main material, a third positive electrode binder, a third conductive agent, a fourth conductive agent and a fourth positive electrode binder in a solvent. The molecular weight of the second positive electrode binder is greater than 1 million and the crystallinity is greater than 45%. The molecular weight of the fourth positive electrode binder is less than 700,000 and the crystallinity is less than 40%; Step S3: according to the surface density of the positive electrode sheet determined in step S1, the first positive electrode slurry is coated on the current collector to form a first positive electrode coating, and the second positive electrode slurry is coated on the first positive electrode coating to form a second positive electrode coating, and then dried to obtain a electrode sheet; Step S4: Roll-press the electrode sheet obtained in step S3 to obtain a high-density thick positive electrode sheet.
11. The preparation method according to claim 10, wherein in step S2, firstly, the second conductive agent and the second positive electrode binder are dispersed in a solvent to form a first conductive slurry, and then the first conductive slurry is mixed with the first positive electrode active main material, the first positive electrode binder and the first conductive agent and dispersed in the solvent to obtain the first positive electrode slurry; and / or, Firstly, the fourth conductive agent and the fourth positive electrode binder are dispersed in a solvent to form a second conductive slurry, and then the second conductive slurry is mixed with a second positive electrode active material, a third positive electrode binder and a third conductive agent and dispersed in a solvent to obtain a second positive electrode slurry.
12. The preparation method according to claim 10 or 11, wherein the surface density of the positive electrode sheet determined in step S1 is 400-800 g / m 2 , preferably 480-630g / m 2 .
13. The preparation method according to any one of claims 10 to 12, wherein in step S2, the viscosity of each of the first positive electrode slurry and the second positive electrode slurry is 4000-6000 Pa·s, the solid content is 68-75% by mass, the average particle size of the slurry particles is less than 60 μm, and the scratch is less than 40 μm.
14. The preparation method according to any one of claims 10 to 13, wherein in step S3, the coating surface density of the first positive electrode slurry is 216-284 g / m 2 The coating surface density of the second positive electrode slurry is 264-347g / m 2 .
15. The preparation method according to any one of claims 10 to 14, wherein in step S4, the roller compaction density is 3.28-3.5 g / cm 3 ; Preferably, the rolling pressure is 45-100T.
16. A lithium ion battery, characterized in that: It includes the thick positive electrode sheet described in any one of claims 1 to 9 or the thick positive electrode sheet obtained by the preparation method described in any one of claims 10 to 15.
Citation Information
Patent Citations
A making method for anode slice of lithium ion battery
CN101241988A